Pure Red Cell Aplasia due to B19 Parvovirus Infection after Autologous Stem Cell Transplantation - Panagiotis Tsirigotis; Konstantinos Girkas; Christina Economopoulou; Anthoula Bouchla; Nikolaos Papanicolaou; Panagiota Economopoulou; Sotirios Papageorgiou; Vassiliki Pappa; John Dervenoulas (Case Reports in Transplantation)
Parvovirus B19 is recognized as a rare cause of pure red cell aplasia (PRCA) in allogeneic stem cell (SCT) and solid organ transplant patients. We report a patient with Hodgkin's disease who developed PRCA due to parvovirus B19 after autologous SCT and who had an excellent response after treatment with gamma-globulin.